PG13 National evaluation of a low-dose, high-frequency cardiac resuscitation quality improvement programme in the United Kingdom – user feedback preliminary findings. (10th November 2020) - Kuyt, Katherine; Fenwick, James; McIntosh, Rod; Withey, Victoria; Chang, Todd; Mackinnon, Ralph
Abstract : Background: High quality CPR has been shown to save lives and has been identified as the 'primary component in influencing survival from cardiac arrest' (1). The UK RQI Programme has been designed to improve resuscitation education for healthcare providers with mandated quarterly CPR training on a specially designed cart in the workplace (RQI, Laerdal Medical). Providing users with simulation training in a 'low-intensity, high-frequency' training program which delivers live feedback and on-going assessments. This work presents the preliminary findings regarding acceptability of the RQI programme to end-users Summary of Work: Acceptability was evaluated using an online questionnaire, containing both closed-ended questions on a 5-point likert scale, and open-ended questions with a free-text box. The questionnaire was hosted on a third party survey site, and the hyperlink to access the questionnaire was sent to users via email who were then able to respond anonymously. Closed-ended questions were evaluated using descriptive statistics, while the responses to open-ended questions were evaluated for common themes. Summary of Results: Thirty-seven users to date, from one hospital, responded to the questionnaire. 75.7% of respondents agreed that the RQI training programme tool had improved their ability to perform CPR. Common themes in response to questions regarding the users' experience of the UK RQI programme were an improvement in confidence and skills, benefits of the regularity of training, and the good quality of feedback. However, some users felt that in person trainers provided better feedback. Additional negative themes centred on a lack of teamwork, and some users finding it difficult to achieve a passing score. 75% of respondents agreed, or strongly agreed that they would recommend the UK RQI programme to a colleague. Discussion and Conclusions: User feedback was overall positive. Many users felt their skills had improved and had increased in confidence in their ability to perform CPR. The negative feedback regarding the difficulty in passing the RQI programme may in fact demonstrate an advantage of the RQI system. Assessment by an instructor has been shown to be subjective and potentially inaccurate regarding the quality of CPR being performed (2). The RQI cart has pre-set parameters, in line with resuscitation council UK guidelines, against which user performance is scored. In conclusion, preliminary findings suggest the RQI programme was well received by most users. Further developments of the RQI programme could work to increase aspects of team-work within the curriculum and explore additional formats for providing feedback. References: Meaney PA, Bobrow BJ, Mancini ME, Christenson J, de Caen AR, Bhanji F, et al. Cardiopulmonary resuscitation quality: improving cardiac resuscitation outcomes both inside and outside the hospital: a consensus statement from the American Heart Association. Circulation . 2013;128(4):417–35. Jones A, Lin Y, Nettel-Aguirre A, Gilfoyle E, Cheng A. Visual assessment of CPR quality during pediatric cardiac arrest: does point of view matter? Resuscitation 2015;90:50–5.